Implant-supported fixed prostheses in the edentulous maxilla: 8-year prospective results - Mertens, Christian; Steveling, Helmut (Clinical oral implants research, 2011)
Objective: The purpose of this prospective study was to evaluate the long-term survival and success rates of implants and screw-retained, full-arch prostheses placed in edentulous maxillae over 8 years of function. Materials and methods: A total of 106 Astra Tech implants were placed in the maxillae of 17 edentulous patients in a one-stage surgical approach. After a healing period of 6 months, the patients received fixed screw-retained bridges. Follow-up visits, including clinical and radiographic examinations, were performed after 6 months and at yearly intervals. Implant survival, implant success, and marginal bone-level changes were defined as the primary outcome variables. The secondary aims were to report periodontal pathogens at 5 years' follow-up and patients' satisfaction at the 8-year follow-up. Results: The overall observation time was 8 years. One patient died during the study and one implant failed during the healing period, yielding an 8-year cumulative implant survival rate of 99%. The prosthetic survival rate was 100%. The mean crestal bone loss amounted to 0.3 ± 0.72 mm. Patients' subjective evaluations demonstrated an overall high level of satisfaction. In all cases, except for one, microbiologic probing of the peri-implant sulcus after 5 years showed no higher incidence of periodontal pathogens. Conclusions: Screw-retained, full-arch restorations on six implants in an edentulous maxilla are a predictable and highly successful treatment concept as observed throughout this study with an observation period of 8 years of function, in particular with respect to low crestal bone loss and high patient satisfaction.
First published: 19 November 2010
Gesehen am 18.08.2022